Obtaining of transgenic french bean plants (Phaseolus vulgaris L.) resistant to the herbicide pursuit by Agrobacterium-mediated transformation - Nifantova, S.N.; Komarnickiy, I.K.; Kuchuk, N.V. (Цитология и генетика, 2011)
The transgenic plants of French bean (Phaseolus vulgaris) resistant herbicide Pursuit and kanamycin have been obtained. The genetic transformation was carried out with Agrobacterium tumefaciens strain LBA4404 containing binary vector carrying mutant ahas/als and selective nptII genes. Integration of the transgenes into plant genome was confirmed by polymerase chain reaction. Получены трансгенные растения фасоли обыкновенной (Phaseolus vulgaris), которые содержат ген ahas/als, обусловливающий устойчивость к гербициду Pursuit. Генетическую трансформацию осуществляли с использованием штамма Agrobacterium tumefaciens LBA4404, который содержит плазмиду pCB004, с мутантным геном ahas/als и маркерным геном nptII, обусловливающим устойчивость к канамицину. Селектирован ряд устойчивых к гербициду Pursuit и канамицину линий. Интеграция перенесенных генов в растительный геном доказана при помощи метода полимеразной цепной реакции. Отримано трансгенні рослини квасолі звичайноі (Phaseolus vulgaris), які містять мутантний ген ahas/als, що обумовлює стійкість до гербіциду Pursuit. Генетичну трансформацію проводили за допомогою штаму Agrobacterium tumefaciens LBA4404 з використанням плазміди pCB004, яка містила мутантний ген ahas/als та маркерний ген nptII, що обумовлює стійкість до канаміцинсульфату. Інтеграція перенесених генів у рослинний геном доведена за допомогою полімеразної ланцюгової реакції.